Assessment of three different parameters of urban ponds at Rajshahi, Bangladesh - Flowra, FA; Ghosh, JK; Tumpa, AS; Jahan, SN (Journal of Bio-Science, 2012)
Context: Physico-chemical factors directly affect the water quality. Biological parameters varied from pond to pond according to the water quality. Objective: To assess the physico-chemical conditions and plankton abundance in the studied ponds. Materials and Methods: The study was carried out for a period of seven months from June, 2008 to December, 2008 in six ponds of Rajshahi Metropolitan area. Surface water samples were collected once a month at 10-11 am in black plastic bottle and analyzed for the estimation of different parameters. Water temperature, transparency, pH, dissolved oxygen (DO), free carbon dioxide (CO2), biological oxygen demand (BOD), nitrite nitrogen (NO2N), nitrite (NO2), toxic ammonia, ammonium ion (NH4+) and total hardness were measured. The density of plankton was also estimated. Results: The mean values of water temperature varied from 28.73 ± 3.98 (Pond 6) to 29.56 ± 4.68°C (Pond 4) and the pH varied from 7.37 ± 0.26 (Pond 6) to 8.57±0.26 (Pond 4). The DO varied 1.66 ± 1.03 (Pond 1) to 4.68 ± 0.36 mg/l (Pond 6) and the mean value of free CO2 varied from 4.29 ± 0.37 (Pond 5) to 50.91 ±19.30 mg/l (Pond 3). The total hardness was 136.79 ± 20.28 (Pond 6) to 183.14 ± 51.17 mg/l (Pond 3) with NO2varied from 0.003 ± 0.002 (Pond 5) to 2.08 ± 0.59 mg/l (Pond 4). The mean total phytoplankton was 28761.43 ± 2912.62 (Pond 2) to 63629.29 ± 20214.44 cells/l (Pond 4) and the mean total zooplankton was 13314.24 ± 3189.70 cells/l (Pond 5) to 18820.00 ± 932.51 cells/l (Pond 4). Conclusion: The deterioration in the physico-chemical quality and plankton population observed in this study is alarming, and periodic monitoring and preventative measures are required to save the aquatic system from eutrophication. DOI: http://dx.doi.org/10.3329/jbs.v19i0.13002 J. bio-sci. 19 59-63, 2011